2015
DOI: 10.1016/j.nanoen.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Revealing and suppressing surface Mn(II) formation of Na0.44MnO2 electrodes for Na-ion batteries

Abstract: Understanding and controlling the surface activities of electrode materials is critical for optimizing the battery performance, especially for nanoparticles with high surface area. Na 0.44 MnO 2 is a promising positive electrode material for large-scale sodium-ion batteries. However, its application in grid-scale energy storage requires improvements in cycling stability at high rate. Here, we performed comprehensive surface-sensitive soft x-ray spectroscopic studies of the Na 0.44 MnO 2 electrode. We are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 42 publications
8
104
1
Order By: Relevance
“…In all, considering the cost of scaling up and intrinsic electrochemical performance of the electrodes, O3-Na 0.9 Cu 0. 22 6 and Na x MnFe(CN) 6 exhibit as the most promising candidates for commercial application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, considering the cost of scaling up and intrinsic electrochemical performance of the electrodes, O3-Na 0.9 Cu 0. 22 6 and Na x MnFe(CN) 6 exhibit as the most promising candidates for commercial application.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent electrochemical performance of Na 0.44 MnO 2 nanowires benefits from shortened diffusion path of Na ions and stable tunnel structure. After that, a lot of Na 0.44 MnO 2 materials with different nanostructures have been realized [21][22][23]. The sodium storage mechanism has also been studied.…”
Section: Tunnel-type Oxidesmentioning
confidence: 99%
“…They also revealed that cycling above 3 V could efficiently suppress the Mn 2+ formation, preventing capacity fading. [100] Cai et al have synthesized monoclinic Na 0.282 V 2 O 5 nanorods by a facile hydrothermal method, containing 3D tunnels along the b-axis. As an SIB cathode material, Na 0.282 V 2 O 5 delivered a discharge capacity of 104 mA h g −1 at 0.3 A g −1 in the range 1.5-4 V with a good capacity retention of 79% over 1000 cycles.…”
Section: Sodium-inserted Tunnel Metal Oxidesmentioning
confidence: 99%
“…More recently, NMO materials have also been prepared by other synthesis procedures such as wet-chemistry techniques [12], including modified-Pechini methods [16][17][18], spray pyrolysis [19], polyvinilpyrrolidone (PVP)-assisted gel combustion synthesis [20,21], and reverse microemulsion methods [22,23]. However, even if a solution precursor is used, the NMO materials are usually obtained at high temperatures between 800 • C [12,17,18] and 950 • C [16,20,21] after several hours of annealing, typically ranging between 8 and 15 h. Notable exceptions are related to hydrothermal preparation strategies, where typically an aqueous solution is heated at only 205 • C, but for 4 days, in an autoclave [24,25]. Quite surprisingly, NMO materials deliver similar electrochemical performance and specific capacities at low current rates (i.e., approaching the theoretical capacity of 121 mA h g −1 ), despite being synthesized via different methodologies.…”
Section: Introductionmentioning
confidence: 99%